1950
DOI: 10.1242/jeb.27.1.73
|View full text |Cite
|
Sign up to set email alerts
|

The Function of Haemoglobin in Chironomus Plumosus Under Natural Conditions

Abstract: 1. The behaviour of final-instar larvae of Chironomus plumosus housed in U-shaped glass tubes was observed at various concentrations of dissolved oxygen and carbon dioxide. 2. Respiratory behaviour, consisting of intermittent irrigation of the tube, alternates with periods of filter-feeding or complete immobility. In well-aerated water about 50% of the time is occupied by respiratory behaviour, 35% by filter-feeding and the remainder by periods of rest. As the oxygen concentration in the water d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1955
1955
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…For example, aquatic P O 2 was found to vary tenfold in a shallow, sun-exposed pool (Figure 3), where increased temperature and consequent reduction in the solubility of O 2 and the increase in dissolved O 2 worked in tandem to create a hyperoxic P O 2 during the daytime (135). The few studies investigating direct effects of ambient hypoxia on aquatic insects have shown shifts in time budgets, with increased time spent on ventilation and concomitant reductions on other activities such as feeding (127,140). Aquatic insects differ widely in their ability to survive hypoxic exposure (127,133), and such differential survival likely underlies shifts in assemblage composition.…”
Section: Environmentally Hypoxic Habitatsmentioning
confidence: 99%
“…For example, aquatic P O 2 was found to vary tenfold in a shallow, sun-exposed pool (Figure 3), where increased temperature and consequent reduction in the solubility of O 2 and the increase in dissolved O 2 worked in tandem to create a hyperoxic P O 2 during the daytime (135). The few studies investigating direct effects of ambient hypoxia on aquatic insects have shown shifts in time budgets, with increased time spent on ventilation and concomitant reductions on other activities such as feeding (127,140). Aquatic insects differ widely in their ability to survive hypoxic exposure (127,133), and such differential survival likely underlies shifts in assemblage composition.…”
Section: Environmentally Hypoxic Habitatsmentioning
confidence: 99%
“…Furthermore, in line with our observations, Kim et al [34] reported that the genera Chironomus, Dicrotendipes, Glyptotendipes, Michrochironomus, Polypedilum, Stictochironomus, Tanytarsus, and Propsilocerus were most abundant in large South Korean rivers. Individuals in these genera can thrive in large rivers because of their adaptive larval and pupal traits such as hemoglobin production, and specific behaviors such as the construction of tubes and burrows in fine sediments [35][36][37]. Moreover, most of the species identified in our study are resistant to eutrophication, and some genera are highly resistant to hypoxia, a frequent phenomenon occurring in polluted streams and benthic zones in lentic areas of large rivers in Northeast Asia.…”
Section: Discussionmentioning
confidence: 79%
“…We sampled the headspace gas for measuring CH 4 and CO 2 concentrations through a connector in the lid and measured dissolved O 2 concentration in the water through contactless sensors (PyroScience GmbH, Germany) at 2 cm above the sediment surface. The relatively large headspace volume provided sufficient oxygen for maintaining the concentration of dissolved oxygen in the water well above 30% saturation, which has been reported as a threshold for alterations of the bioturbating activity of chironomid larvae [33,34]. To ensure gas equilibration between the water and the headspace, we continuously aerated the water with headspace air using an internal air pump and a submerged bubble diffusor (Fig 1).…”
Section: Experimental Designmentioning
confidence: 99%